Time Resolved 3D MRA. Applications for Interventional Neuroradiology - Stracke, CP. (Centauro S.r.l., 2006)
The decision for endovascular treatment of cranial dural AV fistulae and angiomas and their follow-up after treatment is usually based on conventional DSA. New techniques of magnetic resonance angiography (MRA) facilitate high temporal and spatial resolution images. The purpose of this study was to evaluate the applicability and clinical use of a newly developed 3D dynamic MRA protocol on a 3T scanner for neurointerventional planning and decision making. Using a 3T whole body scanner, a three-dimensional dynamic contrast enhanced MRA sequence with parallel imaging, and intelligent k-space readout (Keyhole and "CENTRA" k-space filling) was added to structural MRI and time-of-flight MRA in seven patients. DSA was performed in each patient following MR examination. In all patients MRA allowed the identification and correct classification of the vascular lesion. Hemodynamic characteristics and venous architecture were clearly demonstrated. Larger feeding arteries could be identified in all cases. Smaller feeding vessels were overlooked in dynamic MRA and only depicted in conventional DSA High temporal and spatial resolution 3D MRA may correctly identify and classify fistulae and angiomas and help to reduce the number of pre or post-interventional invasive diagnostic angiograms.